Quantifying the tuneable interactions between colloid supported lipid bilayers - Giakoumatos, Emma C.; Gumí Audenis, Berta; González García, Álvaro; van Hazendonk, Laura S.; Friedrich, Heiner; Tuinier, Remco; Voets, Ilja K. (Frontiers in Soft Matter, 2023)
Colloid supported lipid bilayers (CSLBs) are formed via the rupture and fusion of lipid vesicles to coat spherical colloidal particles. CSLBs are an emerging vector for the controlled self-assembly of colloids due to the ability to include additives into the bilayer, which influence the (a)specific interactions between particles. To evaluate the specificity of CSLB assembly, first a fundamental study on the tunability of the colloidal interaction and resulting colloidal stability of CSLBs without specific interactions is reported here. It was found that both fluid and gel CSLBs showed significant clustering and attraction, while the addition of steric stabilizers induced a profound increase in stability. The interactions were rendered attractive again by the introduction of depletion forces via the addition of free non-adsorbing polymers. The compositions of fluid and gel CSLBs with 5% membrane stabiliser were concluded to be optimal for further studies where both colloidal stability, and contrasting membrane fluidity are required. These experimental findings were confirmed semi-quantitatively by predictions using numerical self-consistent mean-field theory lattice computations.